RELASI TEOLOGI ASWAJA DENGAN HAM PERSPEKTIF KIAI SAID AQIL SIROJ - Harianto, Budi (Humanistika : Jurnal Keislaman, 2018)
Budi HariantoÂ Â Abstract: The definition of Ahl al-Sunnah Wa al-Jamaah resulted from the construction of Kiai Said Aqil Sirojs thought ie Ahl al-Sunnah Wa al-Jamaah as manhaj al-fikr al-din al-syamil ala syuun al-hayat wa muqtadhayatiha al-qaim ala asas al-tawassuth wa al-tawazun wa al itidad wa al-tasamuh (a method of religious thought that encompasses all aspects of life and stands on the principle of equilibrium in aqidah, mediator and adhesive in social life, and justice and tolerance in politics). Kyai Said Aqil Sirojs typology of thought is an inclusive (open) religious typology and the Ahl al-Sunnah Wa al-Jamaah perspective of Kiai Said can be said of the inclusiveness of Ahl al-Sunnah Wa al-Jamaah. So Ahl al-Sunnah Wa al-Jamaah must contain tawasut, tasamuh, tawazun and itidal in acting or thinking. So as to respond to new things in modern life such as human rights. Keywords: HAM, Ahl as-Sunnah Wa-al Jamaah, Justice, Freedom, Equality.